Peningkatan Keterampilan Berbicara Menggunakan Teknik Bercerita dan Berpidato pada Mahasiswa Program Studi Pendidikan Bahasa Indonesia FKIP Universitas Bengkulu - Agus Joko Purwadi; Didi Yulistio (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
The purpose of this study was to describe the improvement of speaking skills using storytelling techniques and making speeches by students of the Indonesian Language and Literature Study Program, FKIP University of Bengkulu. The research method used is a classroom action research method with the Hopkins model which was implemented in two cycles. Each cycle is carried out through four stages including the planning stage, the action stage, the observation stage, and the reflection stage. The data sources of this research were 34 students of the S-1 Indonesian Language and Literature Education Study Program, Bengkulu University, semester II class A. The data of this research are in the form of students' performances in making speeches and telling stories. The data collection technique is in the form of a speaking test, namely making speeches and telling stories. The data analysis used the mean formula and the final analysis was qualitative. The results showed that there was an increase in speaking skills using storytelling techniques and speaking to students. This can be seen from the process and learning outcomes in the first cycle with an average score of 71.88 in the good category, increasing in the second cycle with a score of 81.18 for the very good category. In particular, this increase occurred in storytelling skills with a score of 72.9 in the good category, and speech with a score of 70.85 in the good category, increased in cycle II for storytelling skills with a score of 80.7 in the very good category and speaking with a score of 81.65 in the very good category. . This improvement in speaking skills was followed by an increase in student activity in the learning process in cycle I with an increasing active attitude in cycle II being very active in an attitude of integrity, independence, discipline, responsibility, and honesty.